Possible Electrical Stimulation on Rostral Ventrolateral Medulla That Causes Significant Hypertensive and Tachycardic Changes during Endovascular Treatment of a PICA Aneurysm Abutting the Left Medullary Sulcus - Ozer, Harun (AJNR Am J Neuroradiol, 2005)
Summary: We report the case of a 43-year-old man who underwent endovascular treatment for posterior inferior cerebellar aneurysm. Significant hemodynamic changes were observed as electric stimulation was applied during coil detachment for a PICA aneurysm. We postulate that changes in heart rate and blood pressure during coil detachment were due to the electric stimulation of the tonic vasomotor center located in the rostral ventrolateral medulla, which was very close to the PICA aneurysm.